Strategi Komunikasi Interpersonal Dalam Hubungan Long Distance Marriage Pada Pasangan Suami-Istri - Eldiana Putri Cahyani; Mega Satria Nurul Falah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2026)
The phenomenon of long distance marriage has increasingly emerged as a consequence of economic demands and occupational mobility, particularly in rural areas. This condition requires married couples to develop effective interpersonal communication strategies in order to maintain marital harmony despite physical separation. This study aims to examine the interpersonal communication strategies employed by married couples in sustaining harmonious relationships within the context of long distance marriage in Sugihan Village, Solokuro District, Lamongan Regency. This research adopts a qualitative approach using a phenomenological method to explore the lived experiences of couples engaged in long-distance marital relationships. Data were collected through non-participant observation, in-depth interviews, and documentation. The research informants consisted of married couples practicing long distance marriage as well as supporting informants. Data analysis was conducted using the interactive model proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that couples implement various interpersonal communication strategies to preserve marital harmony, including openness and honesty in communication, flexible utilization of communication technology, emotional and conflict management, adjustment of communication timing, and reinforcement of trust and emotional support. Despite encountering obstacles such as differing work schedules, limited time availability, and technical disruptions, couples are able to manage these challenges through mutual understanding and adaptive communication practices. This study underscores that the quality of interpersonal communication plays a crucial role in maintaining harmony in long distance marriage relationships.